HOW DO YOU SPEAK ENGLISH FLUENTLY? - Halimjonova Muslima Karimjon qizi; Mannobov Abdumalik Mansurjon oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, reflects on the universal challenge of learning to speak English fluently. Drawing on her own experience and the guidance of her English teacher, the author shares three practical habits that transformed her ability to communicate with confidence: daily writing practice, consistent vocabulary building, and speaking aloud in front of a mirror. The article encourages young learners never to fear mistakes and to treat language learning as a lifelong pursuit rather than a temporary task.